Approach-Avoidance Conflict in Learning Mathematics Synchronously - Kiki Henra; Ika Nirmala Masliah (BIRCU, 2021)
The purpose of this study is to provide an overview of the intrapersonal conflicts among students that occurred while learning mathematics online synchronously. This research uses descriptive methods with a qualitative approach. The implementation of this research at SMA Negeri 3 Wajo in grade XI students who conducted online learning using Zoom. The data collection process is conducted using questionnaire instruments, observation sheets, and interviews. The results showed that intrapersonal conflict still occurs in students when learning mathematics online synchronously, based on the results of interviews, students experience Approach-approach, Avoidance-avoidance, and Approach-avoidance they experience a condition of tension, anxiety, fear, and confusion when given question or question. The leading cause of intrapersonal conflict experienced by the student is the thought that learning mathematics is scary. 77.3% of students feel afraid when told to answer math problems by teachers, especially learning materials conducted online that are not able to be understood properly because of network technical constraints. Based on the results of the questionnaire, 72.2% of students experienced network problems while learning math online synchronously.